Quality Evaluation and Phytochemical Screening of Kaempferia galanga and Zingiber zerumbet Rhizome Extracts - Yulius Evan Christian; Ema Hermawati; Rahmatul Qodriah; Mega Efrilia; Senny Listy Kartika Falestin; Pra Panca Bayu Chandra; Sabrina K. Whardhani (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Indonesia has rich biodiversity that provides potential sources of traditional medicine, including Kaempferia galanga and Zingiber zerumbet rhizomes, which are widely used in ethnomedicine. This study aimed to evaluate the quality parameters and phytochemical constituents of both rhizomes in accordance with pharmacopoeial standards. The research involved simplicia preparation, extraction using 96% ethanol by maceration, and subsequent quality testing, including specific, non-specific, and phytochemical screening. Macroscopic and microscopic examinations confirmed the authenticity of the rhizomes, and purity tests showed that foreign organic matter levels were within the acceptable limits (≤2%). The extractive values demonstrated that K. galanga had a higher water-soluble content, whereas the two species had comparable ethanol fractions. Specific and non-specific quality parameters were quantitatively determined in compliance with the Indonesian Herbal Pharmacopoeia. The water-soluble extractive value was 11.30% for K. galanga and 9.20% for Z. zerumbet, while ethanol-soluble extractive values were both 5.30%. Loss on drying and moisture content remained below 10% for both rhizomes, meeting the required threshold. Specific gravity values of 0.8367 g/mL (K. galanga) and 0.79 g/mL (Z. zerumbet) indicated proper extract concentration. These parameters confirm the extracts' quality, stability, and suitability for further phytopharmaceutical development.